High Variability in the Exposure of Baclofen in Alcohol‐Dependent Patients. (22nd August 2013) - Marsot, Amélie; Imbert, Bruce; Alvarez, Jean‐Claude; Grassin‐Delyle, Stanislas; Jaquet, Isabelle; Lançon, Christophe; Simon, Nicolas
<x xml:space="preserve">Abstract</x> Background Baclofen is a GABA‐B receptor agonist used in the treatment of spasticity. Recently, baclofen is used out of its label to decrease craving of alcoholic patients. Its optimal use in these patients requires further pharmacokinetic information. The objective of this study was to characterize the pharmacokinetics of baclofen in alcohol‐dependent patients. Randomized clinical trials are ongoing to evaluate the efficacy for this new indication. Methods Thirty‐seven outpatients (weight: 74.0 kg [42.0 to 104.0]; age: 49 years [31 to 68]) followed in the addictology unit were studied. Total mean dose of 77.9 mg (30 to 240) per day was administered by oral route. Therapeutic drug monitoring allowed the measurement of 139 plasma concentrations. The following covariates were evaluated: demographic data (age, body weight, height, sex), biological data (creatinine, urea, AST, ALT, albumin, PR, VGM, PAL, CDT, GGT), and tobacco consumption (number of cigarettes and Fagerstrom test). Pharmacokinetic analysis was performed by using a nonlinear mixed‐effect population model (NONMEM 7.2 software). Results Data were modeled with a 1‐compartment pharmacokinetic model. The population typical mean (95% confidence interval [95% CI]) values for clearance (CL), apparent volume of distribution (V), and rate constant of absorption (Ka) were 9.9 l/h (9.0 to 11.1), 80.7 l (63.6 to 96.9), and 4.6/h (1.5 to 19.9), respectively. The interindividual variability of CL (95% CI) and V (95% CI), and residual variability (95% CI) were 56.0% (47.9 to 60.7), 68.3% (48.7 to 80.1), and 0.096 mg/l (0.079 to 0.107), respectively. Conclusions Baclofen exhibited a linear pharmacokinetics with a proportional relationship from 30 to 240 mg per day, the dose range currently used in alcoholic patients. A wide interpatient variability was observed which could not be explained by the covariates. This high variation of baclofen exposure may explain the lack of response observed for some patients.